Effect of extruder elements on fiber dimensions and mechanical properties of bast natural fiber polypropylene composites. Issue 12 (29th January 2014) - El‐Sabbagh, Ahmed Mohammed Moneeb; Steuernagel, Leif; Meiners, Dieter; Ziegmann, Gerhard
ABSTRACT Illusions and facts about aspect ratio and the corresponding mechanical properties of the polypropylene flax are studied in this work. Selection of extruder elements controls significantly the fiber final dimensions. Hence, the load transfer efficiency can be improved. Different extruder layouts are tried. First and second trials investigate the mixing degree effect using kneading elements with eight and four kneading elements, respectively. The third and fourth trials keep four kneading blocks but differentiate in using multiprocessing element MPE and toothed elements, respectively. All the four configurations are tested at different shearing rates namely 100, 200, and 300 rpm and different fiber loadings 10, 20, and 30 wt %. Polypropylene (PP) with high flowing properties and slivers flax natural fibers are used. The output extruded strands are mechanically tested. The third and fourth configurations showed superiority to the normal kneading profiles regarding the mechanical properties. Samples of composites are withdrawn after each processing extruder element to study the effect of this element on the fiber dimension. Measurement of extracted fibers is carried out by two methods namely dynamic image analysis machine and secondly normal microscopic investigation. Weibull distributions are defined for fiber geometry distributions for the different locations on the extruder configuration. Also, the effect of the shear rate and the extruder configuration on the final dimensions of the fibers extracted from the composite. The results show the correlation between extruder configuration and fiber aspect ratio and hence the composite overall strength. However, further processing like injection molding erases the pre‐extrusion effect. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40435.